The pharmaceutical quality of brands of metformin tablets in Ogun-State, Nigeria (2014)
The pharmaceutical quality of randomly selected brands of metformin tablets used (prescribed or dispensed) by Community Pharmacists and Doctors in Ogun state, southwestern Nigeria, were evaluated. Eight brands were randomly procured from community pharmacies after administering a pre-tested semi-structured questionnaire to 100 Pharmacists and 15 Physicians across different local government areas in Ogun state, South Western part of Nigeria. The physicochemical properties of the different brands were analysed using the Pharmacopoeia standard. The results showed that Pharmacists’ choice of stocking was based mainly on clients’ demand and quality, while doctors prescribe what is made available by the hospital pharmacy. Out of the eight brands assessed, seven are pharmaceutically equivalent and can be substituted for one another. However, there were quality variations from brand to brand. The ranking of crushing strength for the metformin brands was H>>>G>E>F>D>B>C>A, while the trend for friability was D>>>E>C>H>A>G>F>B. The trend of disintegration time among the brands was D>G>C>E>A>F>B>H and ranking of CSFR/DT was H>>B>F>G>A>E>C>>D. Two brands (D and E) failed the friability test while brand D had significantly lower balance of mechanical and release properties as determined by CSFR/DT. There is therefore a continuous need for random assessment of the quality of metformin brands by regulatory bodies to ensure compliance to specifications. `